BEST EMPLOYEE ASSESSMENT USING WEIGHTED PRODUCT METHOD BASED ON MOBILE WEB AT PUTRI COLLECTION TANGGAMUS - Renaldo, Riki (IJISCS (International Journal of Information System and Computer Science), 2024)
In the present, to reach maximum profit place business No only think of a strategy in increase profit, for place business operating in the field sales and add amount customer for companies engaged in the field services. Therefore That needed source Power competent human in their field. Decision support system is a computer-based system that can be designed to assist in the decision-making process regarding the results. election employee best in place business sale of Putri Collection. In doing so election employee best done use method Weighted Product is a method used to find the optimal alternative from a number of alternatives with a number of certain criteria through weighted multiplication of the performance rating of each alternative on each attribute. In the selection employee best used criteria discipline, skill, responsibility answer, attendance, cooperation. After done calculation use method Weighted Product t is available mark alternative employees who get mark highest become employee best V4 with weight 0.27118.